Novel B-cell subsets in atherosclerosis. Issue 5 (October 2016) - Douna, Hidde; Kuiper, Johan
Abstract : Purpose of review: The number of deaths associated with cardiovascular disease remains high, despite great advances in treating the associated high levels of cholesterol. The main underlying pathology of cardiovascular disease is atherosclerosis, which is recognized as a chronic autoimmune-like inflammatory disease. Hence, there is a pressing need to shed light on the immune pathways associated with atherosclerosis. B cells have long been thought to have a general protective effect in atherosclerosis. However, findings in the last decade have challenged this paradigm, showing that it is crucial to differentiate between the various B-cell subsets when assessing their role/effect on atherosclerosis. Recent findings: It has become increasingly recognized lately that B cells can have significant effects on the immune system independent of antibody production. The understanding that B cells form a major source of cytokines and can directly influence T-cell responses via surface markers, have led to the identification of novel B-cell subsets. These subsets are important modulators of autoimmune disorders but have not yet been fully investigated in atherosclerosis. Summary: Here we review the current known roles of B-cell subsets and the putative effects of recently identified B cells on atherosclerosis.